Petrogenesis of mesoarchean high-K rocks in the Kaapvaal Craton: investigating the Boesmanskop alkaline complex and Salisbury Kop batholith - Leandro, Marcel Vinicius Santos (Stellenbosch : Stellenbosch University, 2026)
Thesis ( PhD)--Stellenbosch University, 2025.